The Results of Toxoplasma gondii Examination IgM Antibodies Using ICT Method and ELISA Method in Pregnant Women - Syifa Amelia Nadayang; Rizana Fajrunni'mah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Toxoplasmosis is a disease that can infect animals and zoonotic in humans. In pregnant women (congenital toxoplasmosis), the risk and severity of symptoms of congenital toxoplasmosis are more severe if infection occurs early in pregnancy and asymptomatic. The only way to determine disease is by serological screening. Serological diagnosis techniques for toxoplasmosis include ELISA (Enzyme-linked Immunosorbent Assay) and ICT (Immunochromatography Assay Test). However, until now, research on toxoplasmosis with the ICT method is still minimal. This study aims to analyze the results of the IgM antibody examination Toxoplasma gondii using the ICT method with the ELISA method and calculate the sensitivity and specificity of the ICT method and the ELISA method in pregnant women. The research design was used analytic (cross-sectional), with the number of samples is 33 serums. Data from the ELISA method obtained from secondary medical record data and the remaining serum samples were examined by the ICT method by researchers at the Harapan Kita Hospital Laboratory. In the ICT method, two samples (6.1%) were positive, and 31 samples (93.9%) were negative. In the ELISA method, results obtained similar to the ICT method, two samples (6.1%) positive and 31 samples (93.9%) with negative results. Toxoplasmosis examination can be done using the ICT method as the initial serological screening stage, but it not recommended as a diagnosis enforcer.